2017
DOI: 10.11604/pamj.2017.27.25.10120
|View full text |Cite
|
Sign up to set email alerts
|

Childhood tuberculosis: management and treatment outcomes among children in Northwest Ethiopia: a cross-sectional study

Abstract: IntroductionChildhood tuberculosis (TB) treatment is becoming a major challenge in the TB control efforts of the Ethiopian health system. This study assessed childhood tuberculosis management, and treatment outcomes among children who completed anti-TB treatment in Northwest Ethiopia.MethodsA cross-sectional study was conducted among children who completed their anti-TB treatment in Gondar University Referral Hospital and 6 satellite health centers. Data from each child with tuberculosis were obtained from rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
5
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 8 publications
2
18
5
3
Order By: Relevance
“…The successful treatment outcome was poor, far away from the WHO bench mark of 85.0% [12], which contrasts other studies that showed an overall good success rate [14,15,17,18,21,28]. However, some studies reported low treatment success rate higher than our finding which include78.0% by Oloyede et al [19], 77.4% reported by Adejumo et al [21] and 78.9% by Kebede et al [28].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The successful treatment outcome was poor, far away from the WHO bench mark of 85.0% [12], which contrasts other studies that showed an overall good success rate [14,15,17,18,21,28]. However, some studies reported low treatment success rate higher than our finding which include78.0% by Oloyede et al [19], 77.4% reported by Adejumo et al [21] and 78.9% by Kebede et al [28].…”
Section: Discussioncontrasting
confidence: 88%
“…DOTS have been found to be effective and efficient in treating TB [14,26,27], however, the treatment outcome in this study showed that the majority of the children were lost to follow up. This is in contrast to reports from other studies where majority of the children completed treatment [14,15,17,18,21,28]. This may be a reflection of inadequate counselling with poor adherence to medications or poor attitude by the parents resulting to lack of regular follow up to ensure completion of treatment.…”
Section: Discussioncontrasting
confidence: 76%
“…The follow-up period of childhood TB treatment outcomes ranged from 1998 to 2013. Regarding the study area, one study was conducted in the Tigray region [12,17], two in Addis Ababa [16], one in Amhara [15], one in Oromia [13], and one in SNNPRS [14]. Among the included studies, four [12][13][14]16] were conducted with a retrospective cohort study design, and two [15,17] were retrospective cross-sectional.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…8 The available studies of the epidemiology and treatment outcomes of childhood TB in Ethiopia have focused on a few health facilities or urban settings. 2,5,9,10 Child-specific performance data are important for understanding the situation in children, exploring the factors associated with program success, and fostering evidence-based decision-making at the policy, planning, and program implementation levels. However, the national health management information system routinely reports aggregated treatment outcomes for all age-groups.…”
Section: Introductionmentioning
confidence: 99%